Moderating role of technology orientation on the relationship between knowledge management and SMEs’ performance in Oman: a conceptual study - Saqib, Muhammad; Baluch, Nazim Hussain; Mohamed Udin, Zulkifli (International Economic Society, 2017)
In today’s fast-paced, vibrant market situation, Small and Medium Enterprises (SMEs) absolutely play a vital role.Growing and dynamic SMEs are the main drivers and blood cells in the growth and sustainability of any nation’s economy, as they provide ample of opportunities and additional values. A middle-income economy, like Oman, whose SME sector continues to be in its emerging stages, is yet to come to a phase where the SME sector could be one of the key contributors to the nation’s GDP. Knowledge Management (KM) has been used to attain superior performance in organizations since 1990s; however, the implementation of KM in SMEs is its infancy stage and a concern of several researchers around the world. Literature reveals the lack of studies on the implementation and effects of Knowledge Management in SMEs sector. The complexity in implementing a complete KM system is due to the absence of an integrated framework. The aim of this research is to debate the vital effects of Knowledge Management on the performance of Oman SMEs by incorporating Technology Orientation (TO) as the moderating agent. Furthermore, this conceptual research study highlighted the relationship between knowledge management and performance of SMEs in Oman.